Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T18:04:07+01:00
A)-2abc dla a=4 , b= -1/2 c = -5
-2*4* (-½) * (-5) = -2*(-½) * 4* (-5) = 1* (-20) = -20

b)-3x² dla x= - 1/3
-3* (-⅓)² = -3 * ¹/₉ = -⅓

c)1/2 mn dla m = -8 , n = 2½ = ⁵/₂
½ * (-8) * ⁵/₂ = - 4 * ⁵/₂ =-10

d)0,2 yz dla y = -5 , z = -3,2
0,2 * (-5) * (-3,2) = -1 * (-3,2) = 3,2
3 3 3
2010-03-02T18:04:32+01:00
A)=-2*4*(-1/2)*(-5)= -20
b)-3 * (-1/3)^2=-3*1/9=1/3
c)1/2*(-8)*2 1/2=-10
d)0,2*(-5)*(-3,2)=3,2
2010-03-02T18:15:11+01:00
-2*4*(-1/2)*(-5)= -20
-3 * (-1/3)^2=-3*1/9=1/3
1/2*(-8)*2 1/2=-10
0,2*(-5)*(-3,2)=3,2